Integration of electric vehicle parking lots into railway network considering line losses: A case study of Istanbul M1 metro line - Karakus, Furkan; Cicek, Alper; Erdinc, Ozan (ELSEVIER, 2023)
Transportation by traditional vehicles is among the important causes of environmental pollution. In this direc-tion, states are making various moves to increase the number of electric vehicles (EVs) for a sustainable envi-ronment. Moreover, to solve the traffic problem in many countries, the prevalence of rail systems should be increased, and their use should be encouraged. In this direction, it seems reasonable to integrate EV parking lots (EVPL) with rail systems and to give some of the idle transformer power of the rail system to EV chargers. This structure is very reasonable that reducing traffic congestion and making it easier to charge EVs. However, one important thing to consider is that line losses increase due to peak load when charging lots of EVs. In this study, the framework covering the integration of EVPLs with PV into the railway, which aims to minimize the line losses in the objective function, is explained. It is desired to enhance efficiency by managing EVPLs, which are powered by rail system transformers. The proposed structure is modeled with the stochastic approach and mixed-integer linear programming (MILP). Moreover, various case studies are carried out using real data from the Istanbul M1 metro to test the accuracy of the study. It is concluded that with optimum management of EVPLs, line losses can be reduced, and load flows can be relieved. As the most striking result, if the existing PV system is doubled and a parallel line is added, the losses can be reduced significantly, which corresponds to 65.94 %.
Keywords: Electric vehicle; Electric vehicle parking lot; Line losses; Railway system; Photovoltaic power source; REGENERATIVE BRAKING; ENERGY MANAGEMENT; OPERATION; SYSTEM; Energy & Fuels